A standardized database containing information on agronomic Zn fortification trials, inclusing their impacts on yield, grain nutrient content, and agronomic practices wheat in Ethiopia - Sida, Tesfaye Shiferaw (Harvard, 2026)
This dataset compiles Geo-tagged plot-level zinc agronomy and crop quality variables. Treatment fields include Zn_rate (kg ha⁻¹), Zn_source (e.g., ZnSO₄), application_method (basal/foliar/split), application_timing, and co-nutrient rates (N, P, K, S). Crop descriptors cover genotype/variety, season, site, replicate/block, and basic geolocation where available. Soil covariates include pH, OC/TN (%), available P (method-specific), CEC/ECEC (cmolc kg⁻¹), texture (clay/silt/sand, %), and DTPA-Zn (mg kg⁻¹). Plant and grain measurements include grain_Zn and straw_Zn (mg kg⁻¹), leaf_Zn at key stages (mg kg⁻¹), grain_yield (t ha⁻¹), aboveground_biomass (t ha⁻¹), TKW (g 1000⁻¹), harvest_index (%), and, where measured, phytate, phytate:Zn (molar ratio), protein (%), and moisture (%). Derived indicators provide coherent Zn response and efficiency metrics, including Zn_uptake (g ha⁻¹), agronomic_efficiency, recovery_efficiency, physiological_efficiency, and Δgrain_Zn relative to control. Units are standardized across records, and computed indices are derived directly from the primary measurements.